Cultivating complexity: Advancements in establishing in vitro models for the mucus‐adhering gut microbiota - Marco Calvigioni; Diletta Mazzantini; Francesco Celandroni; Giovanni Vozzi; Emilia Ghelardi (Microbial Biotechnology)
Abstract A healthy mucus is essential for maintaining intestinal homeostasis and overall well‐being. In recent years, extensive research focused on understanding the intricate interactions between mucus and the gut microbiota. Mucus‐adhering bacteria play crucial roles in preserving barrier integrity, epithelial permeability and mucus architecture, as well as in the colonization resistance against pathogens. Unravelling the significance of these microorganisms in human health and disease is challenging, primarily because most of the studies on the human gut microbiota rely on faecal samples, which do not fully represent the microecological complexity found in the intestinal mucosa. This review discusses novel strategies to specifically target and evaluate the mucosal microbiota, such as culturomics applied to mucosal biopsies or brushings, intestinal organoids and artificial in vitro models incorporating mucus.